2008
DOI: 10.1111/j.1540-8159.2008.01125.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Sleep Deprivation is Associated with Increased QT Dispersion in Healthy Young Adults

Abstract: In conclusion, we clearly demonstrated that even one night of SD is associated with significant increase in QTmax, QTd, and cQTd in healthy young adults despite remaining within normal limits. These electrocardiographic changes in acute SD might contribute to development and/or recurrence of arrhythmias. This implication deserves further studies for clarifying the possible linkage between SD and arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 36 publications
(45 reference statements)
1
20
1
Order By: Relevance
“…Electrocardiographic abnormalities in cardiac conduction and repolarization resembling a proarrhythmogenic profile have also been detected after acute experimental sleep deprivation 64,65 .…”
Section: Epidemiologic Evidencementioning
confidence: 98%
“…Electrocardiographic abnormalities in cardiac conduction and repolarization resembling a proarrhythmogenic profile have also been detected after acute experimental sleep deprivation 64,65 .…”
Section: Epidemiologic Evidencementioning
confidence: 98%
“…Empirical studies have shown that short sleep time is the reason for possible unfavorable oncologic, endocrinologic, immunologic, and metabolic effects [21,22]. In addition, we have previously demonstrated that even one night of SD is associated with significant increase in electrocardiographic P and QT durations and dispersions [4,23]. However, exact physiopathological ways to elucidate this issue have not been described sufficiently.…”
Section: Discussionmentioning
confidence: 94%
“…(4) Ozer O et al clearly demonstrated that even one night of sleep deprivation significantly increased QT max, QTd & cQTd in healthy young adults despite remaining within normal limits. (6) The present study examined the effects of sleep duration on QT and QTc intervals in normal weight and obese subjects. This present study also supports the hypothesis that sleep deprivation propentiates obesity and increases QTc intervals.…”
Section: Discussionmentioning
confidence: 99%
“…QT interval was measured by computerized measurements from limb lead II. (6) RR interval is the interval between an R wave and the next R wave. The RR interval from the preceding cardiac cycle is measured from the peaks of the R waves to correct the QT interval for heart rate (QTc).QT intervals were corrected with Bazett's formula.…”
Section: Objectivesmentioning
confidence: 99%